2021
DOI: 10.18632/oncotarget.27949
|View full text |Cite
|
Sign up to set email alerts
|

Activation of plasmacytoid dendritic cells promotes AML-cell fratricide

Abstract: Acute myeloid leukemia (AML) is characterized by the proliferation of immature myeloid blasts and a suppressed immune state. Interferons have been previously shown to aid in the clearance of AML cells. Type I interferons are produced primarily by plasmacytoid dendritic cells (pDCs). However, these cells exist in a quiescent state in AML. Because pDCs express TLR 7-9, we hypothesized that the TLR7/8 agonist R848 would be able to reprogram them toward a more active, IFN-producing phenotype. Consistent with this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The use of a TLR7/8 agonist leads to higher CD40 expression and an increase in INF-β production by pDC. Treatment with INF-β led to the upregulation of CD38 expression and a greater cytotoxicity of AML cells in the presence of daratumumab (anti-CD38 antibody) [ 73 ]. Another study about developing a dendritic cell vaccine to be used for therapy of minimal residual disease in acute myeloid leukemia assessed the uptake of apoptotic leukemic cells by monocyte-derived DC (MoDC) and DC after stimulating the TLR7/8 receptor.…”
Section: Toll-like Receptors and Hematologymentioning
confidence: 99%
“…The use of a TLR7/8 agonist leads to higher CD40 expression and an increase in INF-β production by pDC. Treatment with INF-β led to the upregulation of CD38 expression and a greater cytotoxicity of AML cells in the presence of daratumumab (anti-CD38 antibody) [ 73 ]. Another study about developing a dendritic cell vaccine to be used for therapy of minimal residual disease in acute myeloid leukemia assessed the uptake of apoptotic leukemic cells by monocyte-derived DC (MoDC) and DC after stimulating the TLR7/8 receptor.…”
Section: Toll-like Receptors and Hematologymentioning
confidence: 99%
“…Xiao et al showed a significant reduction of plasmacytoid dendritic cells (pDC) in AML patients, as well as blast: pDC ratio correlated with positive measurable residual disease and poor outcome [ 182 ]. On the contrary, elevated DC proportions of peripheral blood mononuclear cells have been reported accompanied by immunosuppressive characteristics [ 122 ], an effect reversed with a TLR7/8 agonist [ 183 , 184 ]. Additionally, tissue forming-pDC (TF-pDCs) positive patients had inferior prognosis [ 185 ].…”
Section: Immune Evasion In Acute Myeloid Leukemiamentioning
confidence: 99%